The Architecture of Distributed Database System in the VANET Environment - Janech, Ján; Kršák, Emil; Toth, Štefan (Informatica, 2014)
This paper describes principles of the data communication in the distributed database system AD-DB developed by the authors. The database system is designed to function properly in such a complex and dynamic network as the VANET is. That way, vehicles connected to the VANET could distribute traffic related data to the others. The paper concludes by proposing a solution for security problems by introducing cross-certificate to our system.